Dampak Penerapan Akuntansi Forensik terhadap Pendeteksian Fraud Pengadaan Barang atau Jasa di Perwakilan BPKP Provinsi Jawa Timur - Muhammad Nabil Fatwa; Maulana Ikhrom Ababil; Teguh Adi Priansyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the impact of forensic accounting implementation on fraud detection in the procurement of goods and services at the East Java Provincial Representative Office of the Financial and Development Supervisory Agency (BPKP). A qualitative case study approach was employed to obtain an in-depth understanding of forensic accounting practices within investigative audits. Data were collected through in-depth interviews with investigative auditors, direct observation of audit processes, and analysis of relevant audit documentation. The findings reveal that forensic accounting contributes significantly to enhancing fraud detection by strengthening investigative audits, utilizing data analytics, conducting comprehensive document reviews, and applying investigative procedures such as interviews and field verification. These practices enable auditors to identify red flags, detect collusive procurement patterns, and substantiate evidence of procurement irregularities more effectively. However, the effectiveness of forensic accounting implementation is constrained by limited forensic-certified human resources, suboptimal use of analytical tools, restricted access to integrated procurement data, and political sensitivity surrounding procurement cases. The study concludes that strengthening auditor competencies, improving analytical infrastructure, and integrating forensic accounting with procurement oversight mechanisms are essential to reinforce fraud detection and promote public sector accountability.